Determination of the Nutritional Profile of Rice Flour Subtituted with Moringa (Moringa oleifera) Leaf Flour as an Intermediate Product - St Hartini Djalil; Irwan Irwan; Ariella Ramadhani Putri; Arfina Sukmawati Arifin; Noor Aliyah Haris (Pattimura University, 2026)
Abstract Rice flour is a widely used as an intermediate ingredient in various processed food products; however, it has limitations in terms of protein and micronutrient ontent. The utilization of broken rice as a by-product of rice processing and the substitution of moringa leaf flour are expected to enhance the protein and micronutrient content of rice flour. This study aimed to evaluate the nutritional profile of rice flour substituted with moringa (Moringa oleifera) leaf flour as an intermediate product for functional food development. Substitution was conducted at moringa leaf flour concentrations of 0%, 5%, 10%, and 15% based on the total flour weight. Proximate analysis was performed to determine moisture, ash, protein, fat, carbohydrate, and dietary fiber contents. The results showed that increasing the proportion of moringa leaf flour significantly increased moisture, ash, fat, protein, and dietary fiber contents, while carbohydrate content decreased with higher levels of moringa leaf flour substitution. These findings indicate that rice flour substituted with moringa leaf flour has strong potential as a nutrient-enriched intermediate product and may support the development of locally based healthy food products. Further studies are recommended to evaluate the physicochemical, functional, and sensory characteristics of final products derived from this composite flour.